THE EFFECT OF STORE BRAND IMAGE AND SERVICE QUALITY TOWARDS CUSTOMER LOYALTY AT FRESHMART SUPERSTORE MANADO - Kumowal, Rivo Christian; Lapian, S. L. H. V. Joyce; Tumiwa, Johan (Universitas Sam Ratulangi, 2016)
Customer loyalty has been recognized as the dominant factor in a superstore’s success. The customer loyalty subject has become of increased interest to most superstore in the competitive situation over the last few years. Store brand image and service quality describes what customers are looking for that is likely to be advantageous to the Superstore. The objectives of this research are to analyze the effect of store brand image, and service quality towards consumer loyalty, simultaneously and partially. Data was analyzed quantitatively and through use of statistical package for social scientists (SPSS). The research method that used in this research is multiple linear regression analysis with the sample of the respondents is 100 samples that were obtained from all the customers who shopping in Freshmart Superstore Manado. The result from this research shown that the store brand image and service quality have a significant effects simultaneously on customer loyalty. Whereas store brand image does have positive effect but not significant partially to customer loyalty. This study reveals that store brand image and service quality in a superstore has a strong effect to bring customer satisfaction, trust, and commitment to being loyal customer. It can improve more by should keep and maintain the worker inside the store, especially in terms make an interesting services at Freshmart Superstore. Keywords: store brand image, service quality, customer loyalty